Unbinding Isaac: the significance of the Akedah for modern Jewish thought - Koller, Aaron J. (The Jewish Publication Society, 2020)
Cover -- Title Page -- Copyright Page -- Contents -- List of Illustrations -- Acknowledgments -- How to Use This Book -- Introduction -- 1. Jewish Experiences of the Akedah -- 2. Kierkegaard -- 3. Jewish Parallels from the Century of Kierkegaard -- 4. Jewish Followers from the Twentieth Century -- 5. Criticizing Kierkegaard -- 6. On Child Sacrifice -- 7. Maimonides and the Complexity of the Divine Will -- 8. Rejecting Child Sacrifice -- Conclusion -- Source Acknowledgments -- Notes -- Bibliography -- General Index -- Index of Texts.